2020
DOI: 10.1523/eneuro.0216-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mouse Claustral Neuron Types Based on Their Intrinsic Electrical Properties

Abstract: Although its dense connections with other brain areas suggests that the claustrum is involved in higher-order brain functions, little is known about the properties of claustrum neurons. Using whole-cell patch clamp recordings in acute brain slices of mice, we characterized the intrinsic electrical properties of more than 300 claustral neurons and used unsupervised clustering of these properties to define distinct cell types. Differences in intrinsic properties permitted separation of interneurons (INs) from pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(91 citation statements)
references
References 48 publications
7
58
0
Order By: Relevance
“…However, the density of PV cell bodies and neuropil labeling decreases drastically in both the dorsal and ventral axes implying that claustrocortical neurons projecting to ALM, MOp, ENTm, and ENTl may receive less prominent PV‐mediated inhibition. The presence of other interneurons containing calretinin, vasoactive intestinal polypeptide (VIP), NPY, SST, and cholecystokinin have been shown to exist in the claustrum (Graf, Nair, Wong, Tang, & Augustine, 2020; Kowiański et al, 2008; Real et al, 2003). Calretinin neurons show a similar spatial distribution to what we describe here for SST (Druga, Salaj, Barinka, Edelstein, & Kubová, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the density of PV cell bodies and neuropil labeling decreases drastically in both the dorsal and ventral axes implying that claustrocortical neurons projecting to ALM, MOp, ENTm, and ENTl may receive less prominent PV‐mediated inhibition. The presence of other interneurons containing calretinin, vasoactive intestinal polypeptide (VIP), NPY, SST, and cholecystokinin have been shown to exist in the claustrum (Graf, Nair, Wong, Tang, & Augustine, 2020; Kowiański et al, 2008; Real et al, 2003). Calretinin neurons show a similar spatial distribution to what we describe here for SST (Druga, Salaj, Barinka, Edelstein, & Kubová, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To isolate cholinergic responses, recordings were performed in the presence of a glutamate receptor blocker (kynurenic acid, KYN; 1 µM) and GABA receptor blocker (Gabazine, GBZ; 10 µM). The claustrum consists of multiple types of projection neurons and interneurons 16 . A trained classifier was applied to whole-cell patch clamp measurements of intrinsic electrical properties to identify neurons that project to cortical or non-cortical targets, as well as to identify the three known types of local interneurons 16 .…”
Section: Main Textmentioning
confidence: 99%
“…Below we briefly describe this model. We first generate synaptic weight matrices W with N = 300 neurons (with excitatory and inhibitory neurons in the ratio 9:1 as empirically determined 36 ) as detailed in Hennequin et al, 2014 31 .…”
Section: Analysis Of Signal and Noise Correlations In Model Cla-like mentioning
confidence: 99%
“…However, with the NPY-GFP mouse used here, there was dense neuropil and cell body labeling that outlined the claustrum core and shell (Figures 12 and 13). A recent study showed that the intrinsic electrical properties of PV, SST, and VIP interneurons in the claustrum were distinct from each other (Graf et al, 2020), similar to cortex. However, to the best of our knowledge, no study has tested or compared the connectivity of SST, NPY, or VIP cells with different claustrocortical connections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the density of PV cell bodies and neuropil labelling decreases drastically in both the dorsal and ventral axes implying that claustrocortical neurons projecting to ALM, MOp, ENTm, and ENTl may receive less prominent PV-mediated inhibition. The presence of other interneurons containing calretinin, vasoactive intestinal polypeptide (VIP), NPY, SST, and cholecystokinin have been shown to exist in the claustrum (Graf et al, 2020;Kowiański et al, 2008;Real et al, 2003).…”
Section: Discussionmentioning
confidence: 99%